PELAKSANAAN UPACARA ADAT BIBU BIYAU PADA MASYARAKAT DAYAK HIBUNT DI DESA KELOMPU - NIM. A1012201053, KALISTA APRILIA YOLANDA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac The marriages of the Dayak Hibunt Community in Kelompu Village, Kembayan District, Sanggau Regency cannot be separated from their relationship with parents, family or relatives, ancestral spirits, or society. Even in the implementation of traditional marriage ceremonies there are still things related to the supernatural, respecting ancestors or forefathers. The implementation of traditional marriage ceremonies which are carried out according to tradition is to maintain and preserve the marriage customs of the Hibunt Dayak Community in Kelompu Village, Kembayan District, Sanggau Regency so that they remain preserved, even though they are experiencing shifts.The problem formulation is